HAPPINESS IN ADOLESCENTS WITH TWO FATHERS AND TWO MOTHERS - Meylin Nur Anggita Putri; Dyah Siti Septiningsih (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study aimed to find happiness in adolescents with two fathers and two mothers. The focus of this research was happiness in them. A qualitative method with a case study approach was used in this study. The participants were the adolescents with two fathers and two mothers and two other informants namely family and close friends of participants. Data credibility used triangulation of sources by comparing data obtained from each source. Triangulation of techniques was conducted by comparing data generated from several different techniques with the same sources. The results discussed and linked the aspects of happiness with the research findings. The results showed that the participants accepted and enjoyed the past, had a positive activity environment, had ambitions in the future, had an effort to achieve goals, had hopes, and a positive point of view on the future.